INNOVATION OF CASSAVA CHOPPING MACHINE WITH A CAPACITY OF 15 KILOS PER HOUR BY ELECTRIC MOTOR - Siswadi Siswadi (TRAKSI, 2022)
So far, cassava cutting is still done traditionally using simple tools and machines. There are several cassava chips entrepreneurs who use simple chopping machines but still do not meet their production capacity, it takes a long time, and the cassava cutting capacity is between 5 kg to 6 kg per hour. Based on the problems above, we aim to develop and innovate to change the cassava chopper system to be practical and efficient so that it can solve problems manually and be more time efficient. The purpose of this study, cassava chips entrepreneurs can use a cassava chopper machine with the result that the cassava cutting capacity increases. The result of this research is a cassava chopper machine with an electric motor specification of 0.5 pk. This chip machine uses a stainless steel blade plate with a diameter of 270 mm and a thickness of 5mm. The transmission system changes the rotation of the electric motor from 1400 rpm to 705 rpm, with components in the form of 2 pulleys, 76.2 mm and 156.2 mm in diameter and connected by a v-belt type A-70. The results of the performance test of the cassava chips machine are able to produce cassava chips 15 kg/hour.